EFFECT OF WORK DISCIPLINE AND COMMUNICATION ON EMPLOYEE PERFORMANCE AT SANTIKA PREMIERE HOTEL SEMARANG - Aprilliyani, Renny; Bambang Kristianto Wibowo (Brilliant International Journal Of Management And Tourism, 2021)
This research was conducted at the Santika Premiere Hotel Semarang which aims to analyze and explain the effect of work discipline and communication on housekeeping performance at the Santika Premiere hotel where the communication dimension has the lowest score. This shows that in reality there are still criticisms and suggestions. This condition is always improved even though the communication is quite good, in order to improve house keeping performance in the future. The research data was obtained through questionnaires and interviews. The sample used in the study was 98 respondents. The results of the study are expected to provide useful information for the manager and guest satisfaction. The data obtained is processed using descriptive analysis and quantitative statistical analysis. Quantitative analysis uses multiple regression analysis to determine the effect of independent variables on the dependent variable, model test, hypothesis test, and yet before the test is done, test the validity and reliability test first. The results of the regression analysis showed that there was an influence of work discipline and communication on housekepping performance at the Santika Premiere hotel. Then the results of the multiple regression analysis test showed a significant F value, with an adjusted R 2 square determination correlation value of 0.486. This shows that the influence of work discipline and significantly influence communication on housekepping performance in Santika Premiere Hotels together with a close relationship of 48.6%.